Serum Response Factor Is Essential for Prenatal Gastrointestinal Smooth Muscle Development and Maintenance of Differentiated Phenotype - Park, Chanjae (J Neurogastroenterol Motil, 2015)
BACKGROUND/AIMS: Smooth muscle cells (SMCs) characteristically express serum response factor (SRF), which regulates their development. The role of SRF in SMC plasticity in the pathophysiological conditions of gastrointestinal (GI) tract is less characterized. METHODS: We generated SMC-specific Srf knockout mice and characterized the prenatally lethal phenotype using ultrasound biomicroscopy and histological analysis. We used small bowel partial obstruction surgeries and primary cell culture using cell-specific enhanced green fluorescent protein (EGFP) mouse lines to study phenotypic and molecular changes of SMCs by immunofluorescence, Western blotting, and quantitative polymerase chain reaction. Finally we examined SRF change in human rectal prolapse tissue by immunofluorescence. RESULTS: Congenital SMC-specific Srf knockout mice died before birth and displayed severe GI and cardiac defects. Partial obstruction resulted in an overall increase in SRF protein expression. However, individual SMCs appeared to gradually lose SRF in the hypertrophic muscle. Cells expressing low levels of SRF also expressed low levels of platelet-derived growth factor receptor alpha (PDGFRα(low)) and Ki67. SMCs grown in culture recaptured the phenotypic switch from differentiated SMCs to proliferative PDGFRα(low) cells. The immediate and dramatic reduction of Srf and Myh11 mRNA expression confirmed the phenotypic change. Human rectal prolapse tissue also demonstrated significant loss of SRF expression. CONCLUSIONS: SRF expression in SMCs is essential for prenatal development of the GI tract and heart. Following partial obstruction, SMCs down-regulate SRF to transition into proliferative PDGFRα(low) cells that may represent a phenotype responsible for their plasticity. These findings demonstrate that SRF also plays a critical role in the remodeling process following GI injury.